Treatment with Saccharomyces boulardii reduces the inflammation and dysfunction of the gastrointestinal tract in 5-fluorouracil-induced intestinal mucositis in mice. Issue 9 (14th May 2014) - Justino, Priscilla F. C.; Melo, Luis F. M.; Nogueira, Andre F.; Costa, Jose V. G.; Silva, Luara M. N.; Santos, Cecila M.; Mendes, Walber O.; Costa, Marina R.; Franco, Alvaro X.; Lima, Aldo A.; Ribeiro, Ronaldo A.; Souza, Marcellus H. L. P.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Intestinal mucositis is an important toxic side effect of 5-fluorouracil (5-FU) treatment. Saccharomyces boulardii is known to protect from intestinal injury via an effect on the gastrointestinal microbiota. The objective of the present study was to evaluate the effect of S. boulardii on intestinal mucositis induced by 5-FU in a murine model. Mice were divided into saline, saline (control)+5-FU or 5-FU+S. boulardii (16 × 109 colony-forming units/kg) treatment groups, and the jejunum and ileum were removed after killing of mice for the evaluation of histopathology, myeloperoxidase (MPO) activity, and non-protein sulfhydryl group (mainly reduced glutathione; GSH), nitrite and cytokine concentrations. To determine gastric emptying, phenol red was administered orally, mice were killed 20 min after administration, and the absorbance of samples collected from the mice was measured by spectrophotometry. Intestinal permeability was measured by the urinary excretion rate of lactulose and mannitol following oral administration. S. boulardii significantly reversed the histopathological changes in intestinal mucositis induced by 5-FU and reduced the inflammatory parameters: neutrophil infiltration (control 1·73 (sem 0·37) ultrastructural MPO (UMPO)/mg, 5-FU 7·37 (sem 1·77) UMPO/mg and 5-FU+S. boulardii 4·15 (sem 0·73) UMPO/mg); nitrite concentration (control 37·00 (sem 2·39) μm, 5-FU 59·04 (sem 11·41) μm and 5-FU+S. boulardii 37·90 (sem 5·78) μm); GSH concentration (control 477·60 (sem 25·25) μg/mg, 5-FU 270·90 (sem 38·50) μg/mg and 5-FU+S. boulardii 514·00 (sem 38·64) μg/mg). Treatment with S. Boulardii significantly reduced the concentrations of TNF-α and IL-1β by 48·92 and 32·21 % in the jejunum and 38·92 and 61·79 % in the ileum. In addition, S. boulardii decreased the concentrations of chemokine (C–X–C motif) ligand 1 by 5-fold in the jejunum and 3-fold in the ileum. Interestingly, S. boulardii reduced the delay in gastric emptying (control 25·21 (sem 2·55) %, 5-FU 54·91 (sem 3·43) % and 5-FU+S. boulardii 31·38 (sem 2·80) %) and induced the recovery of intestinal permeability (lactulose:mannitol ratio: control 0·52 (sem 0·03), 5-FU 1·38 (sem 0·24) and 5-FU+S. boulardii 0·62 (sem 0·03)). In conclusion, S. boulardii reduces the inflammation and dysfunction of the gastrointestinal tract in intestinal mucositis induced by 5-FU.